Beginning Reading Instruction for Elementary School Students Using the Survey, Question, Read, Reflect, Recite, Review (SQ4R) Model - W, Ni Kadek Ayu Putri Lestari; Kristiantari, Maria Goreti Rini; Ambara, Didith Pramuditya (International Journal of Language and Literature, 2024)
The lack of student learning motivation during the learning process caused by the lack of enthusiasm of students when learning is still low. One of the factors that cause the lack of student learning motivation is the use of learning models that are less varied. The purpose of this study was to examine the effect of the Survey, Question, Read, Reflect, Recite, Review (SQ4R) learning model assisted by interactive multimedia on beginning reading skills in Indonesian language in grade I elementary school students. Quasi-experiment research, with a nonequivalent pos-test only control group design with a research population of 211 grade I elementary school students. This research data collection method uses observation. The data analysis technique used descriptive statistical analysis and inferential statistics (t-test). The results of the t-test analysis obtained a t-count value equal to 8.205 and t-table 1.672. Based on the calculation of the t-test obtained t_count more than t_table so that H0 is rejected and H1 is accepted so that there is a significant effect on the application of the Survey, Question, Read, Reflect, Recite, Review (SQ4R) model assisted by interactive multimedia on beginning reading skills in Indonesian Language in grade I elementary school students. The implication of this research is that the application of the SQ4R model assisted by interactive multimedia increases motivation and has a significant impact on the beginning reading skills of grade I elementary school students.